2005
DOI: 10.1073/pnas.0407088102
|View full text |Cite
|
Sign up to set email alerts
|

The neocortical microcircuit as a tabula rasa

Abstract: The neocortex has a high capacity for plasticity. To understand the full scope of this capacity, it is essential to know how neurons choose particular partners to form synaptic connections. By using multineuron whole-cell recordings and confocal microscopy we found that axons of layer V neocortical pyramidal neurons do not preferentially project toward the dendrites of particular neighboring pyramidal neurons; instead, axons promiscuously touch all neighboring dendrites without any bias. Functional synaptic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
142
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(150 citation statements)
references
References 57 publications
7
142
0
1
Order By: Relevance
“…We did attempt to carry out these experiments in adult slices, but these slices do not survive such long-lasting experiments in our experimental conditions. However, it is worth pointing out that, at this age, the axonal and dendritic arborizations have already elaborated to such an extent that all axons are able to be in close apposition with all dendrites multiple times (4,5), which is most likely the essential substrate for microcircuit plasticity. In other words, a major component of microcircuit plasticity requires that the microcircuit has reached a minimal level of axonal and dendritic arborization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did attempt to carry out these experiments in adult slices, but these slices do not survive such long-lasting experiments in our experimental conditions. However, it is worth pointing out that, at this age, the axonal and dendritic arborizations have already elaborated to such an extent that all axons are able to be in close apposition with all dendrites multiple times (4,5), which is most likely the essential substrate for microcircuit plasticity. In other words, a major component of microcircuit plasticity requires that the microcircuit has reached a minimal level of axonal and dendritic arborization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies made an important step toward understanding target selection by showing that the axon of a pyramidal neuron approaches, at a submicrometer distance, the dendrites of every neighboring pyramidal neuron multiple times without any structural bias toward those with which synaptic connections are formed (4)(5)(6). This finding raised the possibility that the microcircuit could be in an all-to-all ''readiness'' to switch rapidly on and off connections between neurons in a form of rewiring plasticity without the axon or the dendrite growing toward a new target.…”
mentioning
confidence: 99%
“…In the present study, we fixed p I and p c so as to account for the neural circuitry of a typical neocortical column. Hence, we used p I = 0.25 [30] and p c = 0.15 [33,29].…”
Section: Connectivitymentioning
confidence: 99%
“…Such units may include mini columns (12, 13), structural columns (14, 15), and a variety of functional columns (16,17). Analysis of neuron morphology (14,(18)(19)(20)(21) has shown that cells within such units have the potential of being connected by structural synaptic plasticity (22-24). However, despite this potential, synaptic connectivity within the units is sparse.…”
mentioning
confidence: 99%